INTERCULTURAL COMPETENCE IN THE TEACHING PROCESS OF A FOREIGN LANGUAGE - Khusniddin, Usmanaliev (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article intends to reflect on the findings of an investigation related to intercultural competence, as an inherent element in the teaching-learning of a foreign proposed from the constructivist paradigm with a qualitative approach, based on the researcher's interpretation, in light of the referenced theoretical foundations, in the pedagogical experience and in the analysis of the data. Some strategies could be defined to incorporate the cultural elements when teaching a foreign language.